Glucose-lowering potential of Guiera senegalensis roots in a diabetic rat model - David Miaffo; Fidèle Ntchapda; Oulianovie Guessom Kamgue; Mahamad Talba Abba; Albert Kamanyi (Mashhad University of Medical Sciences, 2020)
Objective: Guiera senegalensis is distributed in the Sudano-Sahelian zone and used traditionally for the treatment of diabetes. This study was designed to assess the hypoglycemic effects of G. senegalensis in Wistar diabetic rats. Materials and Methods: Phytochemical analysis was carried out on aqueous and methanolic extracts of G. senegalensis. Type 2 diabetes was induced in male rats using nicotinamide/streptozotocin (65 mg/kg/110 mg/kg, i.p.). After diabetes induction, normal and negative control groups received distilled water, positive control group received glibenclamide (0.25 mg/kg) and the others group received aqueous and methanolic extracts (200 and 400 mg/kg, each) orally for 4 weeks. Glycaemia, body weight, insulin level, total cholesterol (TC), high density lipoprotein cholesterol (HDL-c), low density lipoprotein cholesterol (LDL-c), triglycerides (TG), aspartate amino transferase (AST) and alanine amino transferase (ALT) activities, urea and creatinine (Cr) were evaluated.  Results: The content of phenols, flavonoids and tannins were 34.54 mg gallic acid equivalent (GAE)/gE, 4.86 mg quercetin equivalent (QE)/gE and 16.81 mg catechin equivalent (EC)/gE in the aqueous extract, respectively. Phenol (26.01 mg GAE/gE), flavonoid (4.47 mg QE/gE) and tannin (7.67 mg EC/gE) contents were also obtained for the methanolic extract.  G. senegalensis and glibenclamide resulted in a significant increase (p <0.001) in body weight and HDL-c in diabetic group rats receiving glibenclamide and different doses of extracts. . The level of insulin, glycaemia, TG, TC, LDL-c, urea and creatinine significantly decreased (p G. senegalensis extracts. Conclusion: These results confirm the potential of G. senegalensis for the treatment of diabetes and its complications.